Cholinergic Modulation of Large-Conductance Calcium-Activated Potassium Channels Regulates Synaptic Strength and Spine Calcium in Cartwheel Cells of the Dorsal Cochlear Nucleus - He, Shan (Society for Neuroscience, 2014)
Acetylcholine is a neuromodulatory transmitter that controls synaptic plasticity and sensory processing in many brain regions. The dorsal cochlear nucleus (DCN) is an auditory brainstem nucleus that integrates auditory signals from the cochlea with multisensory inputs from several brainstem nuclei and receives prominent cholinergic projections. In the auditory periphery, cholinergic modulation serves a neuroprotective function, reducing cochlear output under high sound levels. However, the role of cholinergic signaling in the DCN is less understood. Here we examine postsynaptic mechanisms of cholinergic modulation at glutamatergic synapses formed by parallel fiber axons onto cartwheel cells (CWCs) in the apical DCN circuit from mouse brainstem slice using calcium (Ca) imaging combined with two-photon laser glutamate uncaging onto CWC spines. Activation of muscarinic acetylcholine receptors (mAChRs) significantly increased the amplitude of both uncaging-evoked EPSPs (uEPSPs) and spine Ca transients. Our results demonstrate that mAChRs in CWC spines act by suppressing large-conductance calcium-activated potassium (BK) channels, and this effect is mediated through the cAMP/protein kinase A signaling pathway. Blocking BK channels relieves voltage-dependent magnesium block of NMDA receptors, thereby enhancing uEPSPs and spine Ca transients. Finally, we demonstrate that mAChR activation inhibits L-type Ca channels and thus may contribute to the suppression of BK channels by mAChRs. In summary, we demonstrate a novel role for BK channels in regulating glutamatergic transmission and show that this mechanism is under modulatory control of mAChRs.